Prospective Model on Enhancing Production of Traditional Grains: Evidence from Zimbabwe - Mvura, Brendon; Muhoyi, Edgar; Situmorang, Dokman Marulitua (GOVERNORS, 2025)
Due to the effects of climate change, rain-fed crop (especially maize) production has been reduced, leading to food insecurity. To mitigate crop failure against negative climate change effects, the Zimbabwean government has promoted the production of traditional grains in drought-prone areas. However, according to national targets, production of these traditional grains has been very low, of recent. Therefore, the main objective of this study is to design a model that can enhance the production of traditional grains in Zimbabwe. Thus, the study investigates factors affecting traditional grain production, examined farmers’ perceptions related to institutional and policy support for traditional grain production and identified problems facing Zimbabwe's traditional grain production. A mixed method approach was utilised, where a questionnaire was administered over a sample of 151 farmers, interviewed from three wards in Nkayi district. Qualitative data were obtained through focus group discussions and key informant interviews. Study findings indicate that sorghum is the major crop grown in the area. Regression analysis results reveal that, area, quantity of fertilizer, quantity of seed, and research and development used in the traditional grain production were statistically significant. The study also found out that the five major constraints of traditional grain production in Nkayi district are, in ranked order; quelea birds, pests, shortage of draught power, seed unavailability; and frequent droughts. Based on these key findings, a model that can be used by both the Zimbabwean government and its key stakeholders to enhance production of traditional grains in Zimbabwe is designed.